Shaping North America : from exploration to the American Revolution - Seelye, James E., Jr; Selby, Shawn; Eisel, Christine (ABC-CLIO, LLC, 2018)
"Compiling famous and hard to find primary sources along with specific topical entries and thematic essays, this book provides an invaluable collection of information about early American history."--Provided by publisher.